In Vitro Antimicrobial Activity of Cinoxacin Against 2,968 Clinical Bacterial Isolates - Jones, R. N. (1976)
Cinoxacin demonstrated effective in vitro antimicrobial activity against the Enterobacteriaceae, but negligible activity against Pseudomonas aeruginosa and gram-positive cocci. The activity of cinoxacin was slightly greater than that of nalidixic acid.